Histopathological mapping of metastatic tumor cells in sentinel lymph nodes of oral and oropharyngeal squamous cell carcinomas. Issue 10 (12th September 2014) - Denoth, Seraina; Broglie, Martina A.; Haerle, Stephan K.; Huber, Gerhard F.; Haile, Sarah R.; Soltermann, Alex; Jochum, Wolfram; Stoeckli, Sandro J.
Abstract: Background: Sentinel lymph node biopsy is a reliable technique for accurate determination of the cervical lymph node status in patients with early oral and oropharyngeal cancer but analyses on the distribution pattern of metastatic spread within sentinel lymph nodes are lacking. Methods: The localizations of carcinoma deposits were analyzed with a virtual microscope by creating digital images from the microscopic glass slides. Results: Metastatic deposits were not randomly distributed within sentinel lymph nodes but were predominant in the central planes closer to the lymphatic inlet. Initial evaluation of the 4 most central slices achieved a high rate of 90% for the detection of micrometastases and of 80% for the detection of isolated tumor cells (ITCs). Conclusion: Based on the distribution we recommend an initial cut through the hilus and to proceed with the 4 most central 150‐µm slices. Complete step sectioning is only required in case of a so far negative result. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1477–1482, 2015